The Effect of Cooperative Learning Model Type Group Investigation on Student Learning Outcomes in Magnitude and Measurement Subjects - Ita Wira Zebua (Asian Journal of Science Education, 2023)
This study aims to determine the effect of cooperative learning model type group investigation on student learning outcomes in magnitude and measurement subjects in Class X SMA Parulian I Medan. The population in this study were all students of class X SMA Parulian I Medan which consisted of 4 parallel classes. The research sample was taken in 2 classes using cluster random sampling consisting of an experimental class of 30 students and a control class of 30 students. The instrument used was a multiple-choice test which consisted of 21 questions. Hypothesis testing using an Independent sample t-test from the results of the pre-test and post-test experimental class and control class. The results of the pretest research obtained the average value of the experimental class at 43.65 and the average value of the control class at 40.57. Based on the normality test Ltable Lcount and homogeneity test Fcount Ftable, this shows that the two classes are normally distributed and homogeneous. Based on the initial ability test t-count t-table indicates that the two classes have the same abilities. Then a different treatment was carried out on the results of the post-test, the average value of the experimental class was 77.30 and the average value of the control class was 72.70, based on the t-test (one party) obtained t-count 2.30 t-table 1.671, so there was a significant influence of the model cooperative learning type investigative group on learning outcomes.